Effect of Reclaimed Asphalt Pavement (RAP) and Used Foundry Sand in Dense Bituminous Macadam (DBM-II) Mix - Mahajan, Shubham (My University, 2019)
In the past 20 years, Reclaimed Asphalt Pavement (RAP) is used worldwide to reduce the use of virgin aggregates in laying new pavements, this helps in reducing the bitumen content, extinction of natural recourses as well as abbreviating energy. When over laying of pavement is done the existing layer is scarped from the surface and considered as waste, thus dumped on the other site. Similar is the Used Foundry Sand which is the waste product of metal casting industries. In this study we are using Reclaimed Asphalt Pavement (RAP) with Used Foundry Sand in asphalt mix of Dense Bituminous Macadam-II with different percentage such that maximum stability and minimum use of binder content for a fair pavement. Will the help of Marshall method of asphalt mix design and Indirect tensile strength test(IDT) it showed at which percentage RAP and used foundry sand showed maximum strength and resistance to cracking. Resilient Modulus values are finding on the basis of IDT results using IRC: 37-(2018). Through this we are able to find the Rutting and fatigue criteria of flexible pavement of Reclaimed Asphalt Pavement (RAP) with Used Foundry Sand. With the use of IIT Pave software we designed a pavement layer with minimum thickness of bituminous layer consisting RAP and used foundry sand. It is analyzed for both critical values of strain values of rutting and fatigue life and their values are less than allowable values as per IRC: 37-2018. Cost analysis for replacement of virgin aggregates with RAP is also analyzed.
Keywords: DBM-II; Stability-Flow analysis; RAP; Used Foundry Sand; Pavement Design IRC:37-2018